Accelerated whole‐brain perfusion imaging using a simultaneous multislice spin‐echo and gradient‐echo sequence with joint virtual coil reconstruction. Issue 3 (8th May 2019) - Manhard, Mary Kate; Bilgic, Berkin; Liao, Congyu; Han, SoHyun; Witzel, Thomas; Yen, Yi‐Fen; Setsompop, Kawin
Abstract : Purpose: Dynamic susceptibility contrast imaging requires high temporal sampling, which poses limits on achievable spatial coverage and resolution. Additionally, more encoding‐intensive multi‐echo acquisitions for quantitative imaging are desired to mitigate contrast leakage effects, which further limits spatial encoding. We present an accelerated sequence that provides whole‐brain coverage at an improved spatio‐temporal resolution, to allow for dynamic quantitative R2 and R2 * mapping during contrast‐enhanced imaging. Methods: A multi‐echo spin and gradient‐echo sequence was implemented with simultaneous multislice acquisition. Complementary k‐space sampling between repetitions and joint virtual coil reconstruction were used along with a dynamic phase‐matching technique to achieve high‐quality reconstruction at 9‐fold acceleration, which enabled 2 × 2 × 5 mm whole‐brain imaging at TR of 1.5 to 1.7 seconds. The multi‐echo images from this sequence were fit to achieve quantitative R2 and R2 * maps for each repetition, and subsequently used to find perfusion measures including cerebral blood flow and cerebral blood volume. Results: Images reconstructed using joint virtual coil show improved image quality and g‐factor compared with conventional reconstruction methods, resulting in improved quantitative maps with a 9‐fold acceleration factor and whole‐brain coverage during the dynamic perfusion acquisition. Conclusion: The method presented shows the advantage of using a joint virtual coil–GRAPPA reconstruction to allow for high acceleration factors while maintaining reliable image quality for quantitative perfusion mapping, with the potential to improve tumor diagnostics and monitoring.